Evaluasi Keragaman Genetik Gen Hormon Pertumbuhan (GH) pada Sapi Pesisir Sumatera Barat Menggunakan Penciri PCR-RFLP - . Jakaria; D Duryadi; R R Noor; B Tappa; H Martojo (Faculty of Animal Science, Bogor Agricultural University, 2007)
A total of 134 Pesisir cattle were genotyped for growth hormone (GH) gene by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The genotype and allele frequencies of the GH MspI and GH AluI Pesisir cattle were determined. The GH MspI gene frequencies for the C and T allele were 0.209 and 0.791 respectively, while GH AluI gene frequencies for the L and V allele were 0.992 and 0.008 respectively. The chi-square analysis indicated that this population is not in Hardy-Weinberg Equilibrium status. Expected heterozygosis value (He) for GH MspI and GH AluI were 0.3306±0.0266 and 0.0149±0.0073 respectively. The PCR-RFLP GH MspI marker has higher genetic variability compare to PCR-RFLP AluI marker. This finding showed that GH MspI T allele was favorable as a GH marker for Bos indicus breeds. Key words: Pesisir cattle, growth hormone gene, PCR-RFLP, polymorphism